Predictors of condom use behavior among men who have sex with men in China using a modified information-motivation-behavioral skills (IMB) model - Hongbo Jiang; Xiaobin Chen; Jing Li; Zhimin Tan; Weibin Cheng; Yi Yang (BMC, 2019)
Abstract Background Men who have sex with men (MSM) are at high risk for human immunodeficiency virus (HIV) infection in China. Correct and consistent condom use is one of the most effective strategies for preventing the spread of HIV. This study developed a modified Information-Motivation-Behavioral Skills (IMB) model to predict condom use behavior among Chinese MSM. Methods A cross-sectional study was conducted to collect data using self-administered electronic questionnaire. Participants were recruited from HIV Voluntary Counseling and Testing clinics in six district Centers for Disease Control and Prevention in Guangzhou and two community-based HIV service centers (Lingnan Partners and Zhitong Charity) from May to September 2017. Structural equation modeling was performed to develop the modified IMB model with extended multilevel factors. Results Among the 976 MSM included, 52.05% had engaged in anal intercourse with a condom every time. The final modified IMB model fitted the data more ideally than the conventional model. The final modified IMB model revealed that behavioral skills positively contributed directly to condom use (β = 0.385, p < 0.001) and partially mediated the associations between information (β = 0.106, p = 0.005) and motivation (β = 0.390, p < 0.001) and condom use. Regarding the extended multilevel factors, education, income, receiving HIV prevention services, sexual partner seeking behavior, depression, intimate partner violence, and child sexual abuse had indirect impacts on condom use that were mediated by information, motivation, and/or behavioral skills (p < 0.05). All paths from the latent variable to the corresponding observed variables were statistically significant (p < 0.001). Conclusion The modified IMB model with extended multilevel factors could serve as a theoretical framework for behavioral interventions for condom use among Chinese MSM. Further prospective studies are needed to examine the predictive power of the modified IMB model.